ARCHITECTURAL ORNAMENTATION OF SIKH HAVELI’S: A CASE STUDY OF NAU NEHAL SINGH HAVELI-LAHORE - Mahrukh Rehman Mirza; Saad Mujahid; Shazia Abro; Shahrukh Noman (International Journal of Contemporary Issues in Social Sciences, 2024)
Architecture ornamentation and the decorative arts displays the aesthetic and cultural dimensions in addition to functionality in the ornamented facades. Historically, these ornamentations not only conveyed the particular architecture style characteristics of specific era rather added the distinguished character to each of them such as the Gothic architecture is known for intricate tracery. Lahore's history is characterized by the impact of multiple governing dynasties, each of which made a unique contribution to the city's architecture and ornamental arts in Pakistan. Sikh era is notable for bringing new ideas, conceptions, and aesthetic preferences, and for making a substantial break from the prevailing environment. The current research is focused on exploring the Sikh architecture ornamentation language for residential architecture (building typology of Haveli’s). The Haveli of Nau Nehal Singh officially known as Government Victoria Girls High School represents one of the finest examples of Sikh architecture in Pakistan, highlighted by the characteristic architecture ornamentation of the Sikh-period, which includes engraved work on bricks in addition to ornate brackets. Through a detailed examination of these elements, this study aims to provide a comprehensive understanding of the artistic, cultural and societal values associated that needs to be preserved for the future generations. The insights will lead towards the pathway for their restorations and preservations.